Analisis Kesadaran Pendaki Terhadap Lingkungan Wisata Pendakian Gunung Tambora - Muhammad Sa'ban; Dalilul Falihin; Feri Padli (UNM Geographic Journal, 2023)
The purpose of this study was to analyze the awareness of climbers towards the tourism environment of Mount Tambora. This study uses a qualitative research model with data collection techniques through in-depth interviews, observation, and documentation. The problems that are the focus of the research are: (1) What is the description of the environmental conditions of Mount Tambora climbing tourism? and (2) How is the awareness of Mount Tambora climbers in protecting the environment for Mount Tambora climbing tourism?. The results of the study show that the environmental conditions of Mount Tambora climbing tourism still require more serious attention from visitors. Climbers of Mount Tambora have a fairly high awareness of keeping the environment clean, but there are still a number of things that need to be improved, such as waste management and toilet management. The conclusion from this study is that climbers' awareness of the tourism environment of Mount Tambora still needs to be improved. In order to maintain the sustainability of the Mount Tambora tourism environment, it is necessary to collaborate between tour managers, climbers and the surrounding community to create a sustainable and sustainable tourism environment.